MHD mixed convective heat transfer in a lid-driven enclosure filled with Ag-water nanofluid with center heater - Mahalakshmi, Thangavelu; Nithyadevi, Nagarajan; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Pergamon-Elsevier Science Ltd, 2018)
The MHD mixed convection inside enclosure with center heater is numerically investigated. The oppositely moving side walls of the enclosure are maintained at constant cold temperature whereas a constant heat source is considered in the bottom wall. The remaining parts of the bottom and top walls are kept adiabatic. The finite volume method and SIMPLE algorithm with power-law scheme is used to solve the governing equations. The present study is concerned with effect of pertinent parameters such as length of heater (F = 0.25, 0.50 and 0.75), Richardson number (Ri = 0.01, 1.0 and 100), Hartmann number (Ha = 0, 25 and 50) and solid volume fraction of nanoparticles on the fluid flow and heat transfer performance of the enclosure. Results are presented with streamlines, isotherms, velocity profiles and average Nusselt numbers. It is observed that heat transfer rate increases as heater length and Grashof number increases whereas heat transfer decrease is found for increasing magnetic field effect. The enhancement rate in heat transfer by increasing the solid volume fraction of nanoparticles is also obtained.
Keywords: Center heater; Finite volume method; Heat transfer; Magnetic field effect; Mixed convection; Nanofluid flow